ANALISIS KINERJA KEUANGAN PADA PT.BANK DANAMON, TBK. - MEIRUNTU INGELIN THERESIA; R. RUNTUWENE; DANTJE KELES (Universitas Sam Ratulangi, 2016)
ABSTRACT : The purpose of this study to analyze financial performance. Bank Danamon Tbk. the years 2011-2015 using CAMEL ratio that includes the capital, assets, management, earnings and liquidity. Implementation of the health assessment PT. Bank Danamon Tbk. done in a way to qualify some of the components of each of the factors, namely components Capital (Capital), Asset (Asset), Management (management), Earning (Profitability), Liquidity (liquidity) or abbreviated terms CAMEL. CAMEL is a crucial factor in the health of a bank predicate. The aspects of one another are interrelated and inseparable. The results of the assessment of financial performance CAMEL ratios indicating that from the aspect of capital owned by PT. Bank Danamon Tbk. turned out to be above 8%, so PT. Bank Danamon Tbk. have sufficient capital to cover all risks arising from the investment of funds in productive assets that support the risk. Then, from the aspect of management as measured by Net Profit Margin found to comply with the provisions of Bank Indonesia and other than that from the aspect of earning and liquidity achieved by PT. Bank Danamon Tbk. in accordance with the provisions of Bank Indonesia. The results showed that the level of health of PT. Bank Danamon Tbk. for 5 years the period 2011-2015 was included in the healthy category. Rate the level of health in 2011 was included in the healthy category with a total credit value of 83.5, in 2012 relatively healthy with a total credit value of 86.25, relatively healthy in 2013 with a total credit value of 90.05, 2014 classified as healthy with total credit score of 91.05 and 2015 are included in the healthy category with a total credit value of 88,13. From the results of the assessment of financial performance and its relation with CAMEL ratio, it can be said that over the last 5 years (2011-2015), which showed that the financial performance achieved by PT. Bank Danamon Tbk. are at a healthy predicate. Keywords: analysis financial performance ratio of CAMEL